Leadership Skills and Wages - Kuhn, Peter; Weinberger, Catherine (Journal of Labor Economics, 2005)
Controlling for cognitive skills, we find that men who occupied leadership positions in high school earn more as adults. The pure leadership‐wage effect varies, depending on definitions and time period, from 4% to 33%. This effect is not an artifact of measurement error in cognitive skills or differences in a wide array of other physical or psychological traits. High school leaders are more likely to occupy managerial occupations as adults, and leadership skills command a higher wage premium within managerial occupations than elsewhere. Finally, it appears that leadership skills may be fostered by exposure to high school leadership opportunities.